IMPLEMENTASI AKAD MURABAHAH PADA PEMBIAYAAN KPR SYARIAH DI BANK MUAMALAT KCP GENTENG - Mira Antika; Munawir Munawir (Jurnal Ekonomi Syariah Darussalam, 2026)
This study aims to examine the implementation of the murabahah contract in Islamic Home Ownership Financing (Kredit Pemilikan Rumah Syariah/KPR Syariah) at Bank Muamalat. This study employed a qualitative research method with a descriptive approach. The results of the study indicate that the implementation of the murabahah contract in KPR at Bank Muamalat KCP Genteng is carried out through several stages, namely financing application by customers, feasibility analysis, financing approval, purchase or acquisition of the house by the bank, and the execution of the murobahah contract, which includes the cost price, profit margin, financing period, and instalment amount agreed upon by both parties. The contract implementation is conducted transparently and in accordance with the procedures applicable in Islamic banking. Implementation of the murabahah contract in Islamic Home Ownership Financing at Bank Muamalat KCP Genteng is in accordance with Sharia principles. This is evidenced by the fulfillment of the pillars and conditions of the murabahah contract, transparency regarding the cost price and profit margin, and the absence of elements of riba, gharar, maisir, and tadlis in its implementation. Keywords: Murabahah Contract, KPR Syariah